Efficacy of Oral Mini Pulse Betamethasone in the Treatment of Vitiligo-A Study in FMCH (Faridpur Medical College Journal, 2016)
Vitiligo is an acquired multifactorial polygenic disorder with a complex pathogenesis, characterized by depigmented macules in skin. A clinical trial was conducted to evaluate the efficacy of oral mini pulse betamethasone in the treatment of vitiligo patients. The study was done in the department of Dermatology and Venereology, Faridpur Medical College Hospital (FMCH), Faridpur, Bangladesh from July 2014 to June 2015. Among thirty patients of vitiligo, most of the male patients (53.33%) and most of the female patients (40%) were between 20 to 25 years of age. Majority of patients (70%) had been suffering from vitiligo for less than 3 years and 50% patients had positive family history. Eighteen (60%) patients had acro-facial type of vitiligo and 20 (66.67%) cases were progressive in nature. In this study, response was slight in 36.67%, moderate in 33.33%, marked in 20% and excellent in 10% of cases after 12 weeks. Eight (26.66%) of total patients were seen to be with clinical side effects. Among the side effects, weight gain 4 (13.33%) was most prevalent, others include general weakness in 2 (6.66%) and acne in 2 (6.66%) patients. In conclusion, oral mini pulse betamethasone seems to be an effective treatment modality to arrest the progression of vitiligo and induction of repigmentation.Faridpur Med. Coll. J. Jan 2016;11(1): 26-29